Variants of the formation and course of drug-resistant epilepsy in children with genetic polymorphisms of CYP2C9, CYP2C19, CYP3A4 - Tantsura, Liudmyla M.; Pylypets, Olena Yu.; Tretiakov, Dmytro V.; Tantsura, Yevhen O. (Wydawnictwo ALUNA, 2023)
To clarify the frequency with which various variants of the formation and course of drug-resistant epilepsy occur in children with genetic polymorphisms of cytochromes CYP2C9, CYP2C19, CYP3A4. Materials and methods: The genotyping of CYP2C9*2, CYP2C9*3, CYP2C19*2, CYP3A4*1B by the allele-specific polymerase chain reaction was performed in 116 children with drug-resistant epilepsy aged from 2 to 17 years. Thirty cases (boys-15; girls-15) with a follow-up period of more than 5 years were analyzed in detail. Results: Of 30 cases analyzed, polymorphisms were not detected in 8 (26.67%) children, and 22 (73.33%) had polymorphisms of the CYP2C9, CYP2C19 and CYP3A4 genes associated with a slow metabolism of AED. In children with polymorphisms of the CYP450 genes, the wave-like course of the disease with the periods of remission and its failures was characteristic, while for children with a presumably normal metabolism there was the initial resistance to the treatment with AED. Conclusions: Individual changes in the AED metabolism affect the course of drug-resistant epilepsies. For patients with a slow metabolism of AED the wavelike course of the disease and the “slipping off” phenomenon were more characteristic.
Keywords: children; drug-resistant epilepsy; cytochrome P450; allelic polymorphism; the course variants